Characterisation of non-cirrhotic MAFLD-related hepatocellular carcinoma: a retrospective cohort study - Shadi Zerehpooshnesfchi; Fatema Safri; Ziyan Pan; Romario Nguyen; Lawrence Yuen; Vincent Lam; Christopher Nahm; Tony Pang; Golo Ahlenstiel; Jacob George; Mohammed Eslam; Liang Qiao (Therapeutic Advances in Chronic Disease)
Background: Hepatocellular carcinoma (HCC) is a major global health issue, in which the underlying liver disease aetiology has shifted towards non-viral causes, particularly metabolic (dysfunction)-associated fatty liver disease (MAFLD). While traditionally associated with cirrhosis, a subset of HCC cases arises in patients with MAFLD but without cirrhosis, whose characteristics remain poorly understood. Objectives: The study aims to explore the clinical, tumour and genetic characteristics of non-cirrhotic MAFLD-related HCC when compared to those that develop in the context of cirrhosis. Design: A multi-centre, retrospective study of 89 MAFLD-related HCC patients enrolled between 2009 and 2023 was performed. Methods: We conducted a study of well-defined MAFLD-related HCC patients to explore their MAFLD-related clinical and genetic associations. Statistical analysis was undertaken to compare the underlying cirrhosis and non-cirrhosis groups for HCC features, adjusting for relevant confounders. Results: Patients with HCC arising in cases of MAFLD without cirrhosis exhibited a lower body mass index, higher triglyceride levels and increased smoking prevalence compared to their counterparts with cirrhosis. Despite arising in the absence of cirrhosis, these patients had more aggressive tumour features, including larger tumour size, multifocality and portal vein thrombosis. Logistic regression confirmed non-cirrhosis status to be an independent predictor of larger tumour size and increased lesion number. Conclusion: Non-cirrhotic MAFLD-related HCC presents with distinct clinical and tumour characteristics, suggesting the existence of unique disease drivers that are yet to be discovered.